Comportamento alimentar da tilápia vermelha (Oreochromis niloticus x oreochromis aureus) arraçoada com diferentes aditivos - Barros, Margarida Maria [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Salaro, Ana Lúcia (My University, 1998)
The objective of this study was to evaluate the attractive capacity and palatability of a commercial extruded diet flavored with the following coats: fish oil (1%); fish oil (1%) + citric acid (.1%); fish oil (1%) + phosphoric acid (.1%); commercial coat (1%) and dendê oil (1%), and the control treatment (absence of coat). The red tilapias feeding behavior was evaluated using a complete randomized experimental design, with 72 observations per treatment. Six 750-L aquariums were used; with three fish (100±.50 g) per aquarium. They had access to the diets, through a couple choice (control x test), in a surface round feeder (feedings), disposed on the opposite lateral of the aquariums. The animals were evaluated during fifteen minutes, twice a day. Due to the use of the chemical substances that did not potencialyzed the feeding response of the red tilapia, it was observed that the usual commercial coat and fish oil did not present an effective addictive to stimulate the ingestion of the extruded diet. Only the commercial coat was lightly capable to provoke confrontation during the feeding process.
Feeding behavior of red tilapia (Oreochromis niloticus x oreochromis aureus) fed with different additives
Keywords: Additive; Feeding behavior; Fish diets